Screening of Diabetes Mellitus and Physical Activity Analysis: A Stepwise WHO Approach - Zata Ismah; Citra Cahyati Nst; Wahidah Wahidah (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
By 2030 it is predicted that there will be 52 million deaths per year due to NCD, an increase of 9 million from 38 million people today. The purpose of this research was to describe the risk factors for NCD in Medan using the stepwise WHO. This research method is a quantitative method with a cross-sectional design. Univariate and Bivariate analysis using the Chi Square test were carried out in this research. 799 participants were recruited using accidental sampling technique. The place of this research was conducted in Medan City, North Sumatra Province. The results of this research indicate that age 55-59 years, last elementary school education, work as an entrepreneur and not eating vegetables are risk factors for diabetes mellitus in this research. It is suggested that local health workers provide health education through outreach to the community, especially the people of Medan City, on how to reduce the risk of increased blood sugar or diabetes mellitus incidence. In addition, participants or the community are expected to be able to maintain a good diet, namely by implementing balanced nutrition, especially paying attention to adequate vegetable consumption.